Peran Tumor Necrosis Factor-Alpha Sistemik pada Respons Imun Toksoplasmosis Okuler - Wahyudi, I Nyoman Surya Ari; Sofia, Ovi (Cermin Dunia Kedokteran, 2025)
Ocular toxoplasmosis (OT) is the most common infection causing posterior uveitis worldwide, caused by the parasite Toxoplasma gondii. Many cytokines such as TNF α, IL-6, and IL-10 are involved in the development of uveitis. Tumor necrosis factor (TNF) is a pro-inflammatory cytokine released primarily during inflammatory response of macrophages and T cells, to mediate the activation and infiltration of leukocytes and T helper (Th)1 lymphocyte responses in the tissue. Macular inflammation caused by TO can lead to substantial visual impairment. High level of TNF-α cause disruption of the blood-retinal barrier in uveitis. TNF-α plays a role as a positive regulator of the immune response. Systemic TNF-α levels in ocular infections, particularly TO, increase, which is associated with an increased inflammatory response, contributing to choroidal and retinal tissue damage in TO patients. The TNF-α levels in tissues and intraocular fluid can vary depending on the type and severity of infection. Detection of systemic TNF-α may act a potential clinical biomarker for ocular toxoplasmosis.